2018
DOI: 10.5301/ejo.5001049
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of 3 exophthalmometers and computed tomographic biometry

Abstract: We demonstrated great accuracy to CT scan biometry with 1-prism Mourits exophthalmometer, low accuracy with the Luedde instrument, and intermediate accuracy with the Hertel exophthalmometer, with fair intraobserver and interobserver reproducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…They could not show an advantage of the parallex-free Mourits exophthalmometer [6]. On the other hand Genders et al as well as Delmas et al indicated good reliability for Mourits exophthalmometer [16, 17]. Further investigation is needed to prove the superiority of Mourits exophthalmometer regarding intra and interobserver reliability.…”
Section: Discussionmentioning
confidence: 99%
“…They could not show an advantage of the parallex-free Mourits exophthalmometer [6]. On the other hand Genders et al as well as Delmas et al indicated good reliability for Mourits exophthalmometer [16, 17]. Further investigation is needed to prove the superiority of Mourits exophthalmometer regarding intra and interobserver reliability.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that the accuracies of three methods are comparative in measuring proptosis without any abnormity. Delmas et al 10 have demonstrated that CT has the same accuracy with Hertel exophthalmometer, but the simple Pythagorean theorem has not been reported yet.…”
Section: Discussionmentioning
confidence: 98%
“…However, the CT is gold standard in measuring proptosis and the Hertel exophthalmometer is commonly used in clinical work. 10,19 The measurement of proptosis by simple Pythagorean theorem has not been reported yet. Our study shows that its accuracy is comparable to CT measurement and Hertel exophthalmometer in normal people.…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that the accuracies of two methods are comparative in measuring proptosis without any abnormity. Delmas et al has demonstrated that CT has the same accuracy with Hertel exophthalmometer [8], but the Heron's formula has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%